Weather Based Information System using IoT and Cloud Computing - Varghese, Aneeta (IJRDO -Journal of Computer Science Engineering, 2015)
Internet of things connect physical world, interact with them and compute the inputs obtained from thephysical scenario. Weather based Information System using IoT and Cloud Computing adopts both theadvantages of cloud computing and internet of things. The proposed system uses sensor network for thedata acquisition and cloud computing platform for storage and processing. Big data is a big concern tointernet of things, which is impossible to handle. The proposed system solves the problem by storing theenormous amount of data in cloud provided datacenters and analyze the large amount of data using kmedoid clustering algorithm. K medoid algorithm outperforms other clustering algorithm when the dataconsists of outliers and noise.